Komunikasi Organisasi Pemimpin Dalam Membangun Kineja Aparatur di IAIN Pekalongan Tahun 2019-2020 - Edy Zubaidi; Mukoyimah Mukoyimah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this research is to find out how much influence the leader communication has to the apparaturs in realizing the mission of the institution in IAIN Pekalongan. The method used is a qualitative field with a case study approach. The case study that the author is doing is intrinsic, the research will focus on organizational communication activities carried out by the leader to the apparatus in the IAIN Pekalongan environment. While data collection using sampling with data analysis study is holistic. Holistic analysis is needed by the writer to describe in detail the communications, the context of the communication, and the setting in which the communication takes place. The result of this research is that organizational communication is carried out on the principles of kinship and culture. This concept encourages the realization of harmonious conditions in the staffing environment of IAIN Pekalongan. Cultural principles are realized in the form of Asah, Asih, and Asuh between the leadership and the apparatus under them. These three principles appear in every formal and non-formal activity, including workshops, Trining, FGD, seminars, istighosah, autbond, dies natalis, and others. Meanwhile, the family principle is realized in daily interactions both in the office and outside the office. Organizational communication by the leader to the apparatus in the IAIN Pekalongan environment is able to encourage the realization of the institution's Vision and Mission.